2023
DOI: 10.3390/ijms24054595
|View full text |Cite
|
Sign up to set email alerts
|

Expression Dynamics of CA IX Epitope in Cancer Cells under Intermittent Hypoxia Correlates with Extracellular pH Drop and Cell Killing by Ureido-Sulfonamide CA IX Inhibitors

Abstract: Carbonic anhydrase IX (CA IX) is a membrane-bound CA isozyme over-expressed in many hypoxic tumor cells, where it ensures pH homeostasis and has been implicated in tumor survival, metastasis and resistance to chemotherapy and radiotherapy. Given the functional importance of CA IX in tumor biochemistry, we investigated the expression dynamics of CA IX in normoxia, hypoxia and intermittent hypoxia, which are typical conditions experienced by tumor cells in aggressive carcinomas. We correlated the CA IX epitope e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…In addition, the prevalence of CA IX expression was notably higher in HCC exhibiting the MTM pattern when compared to other subtypes, in line with findings from a prior study (24). CA IX is not specific to HCCs and its expression is observed in various carcinomas, inducing hypoxic conditions (25)(26)(27)(28). In pathological diagnosis, morphological and immunophenotypic findings as well as high levels of tumor markers can be useful.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the prevalence of CA IX expression was notably higher in HCC exhibiting the MTM pattern when compared to other subtypes, in line with findings from a prior study (24). CA IX is not specific to HCCs and its expression is observed in various carcinomas, inducing hypoxic conditions (25)(26)(27)(28). In pathological diagnosis, morphological and immunophenotypic findings as well as high levels of tumor markers can be useful.…”
Section: Discussionsupporting
confidence: 85%
“…It is found that some antigens or receptors are over-expressed on the surface of tumour cells [107]. Normal cells normally express various receptors like folate, prostate-specific membrane antigen, biotin, transferrin, peptide and carbonic anhydrase IX [108]. Active targeting is based on the specific recognition between receptor and ligand or the covalent modification of targeting groups on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the overexpression of CA IX also provides a clear survival advantage for cancer cells and confers tumor resistance to conventional chemotherapy and immunotherapy. [46,47] In addition, activation of HIF-1 significantly increases CA IX expression in hypoxic environments. Several researches have proved that CA IX could be strongly upregulated by the over expression of HIF-1 and play a central role in hypoxia-mediated tumor heterogeneity.…”
Section: Abnormal Expression Of Ca IXmentioning
confidence: 99%